PENGARUH KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) TERHADAP KINERJA KARYAWAN DI PT. NARENDRA DEWA YOGA KOTA BENGKULU - Rio Pentydia (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2018)
The purpose of writing this thesis is (1) To describe whether there is a significant and positive influence between  emo- tional intelligence (EQ) variable to employee performance variable at PT. Narendra God of Yoga. (2) To describe whether  there is a significant and positive influence between  the variables of spiritual intelligence (SQ) on employee performance variables in PT. Narendra God of Yoga. (3) To describe  whether  there is a significant and positive influence between  emotional intelligence (EQ) and Spiritual Intelligence (SQ) variable to employee performance variable in PT. Narendra God of Yoga. The method used in this research  is descriptive  quantitative research  method, furthermore, the analysis technique using simple linear regression and multiple linear regression,  F test and double  correlation  with the help of computer program SPSS Version 16.0.  The results of this study indicate  that together  there is a significant influence between  emotional intelligence (EQ) and spiritual intelligence (SQ) variable  to employee performance variable  at PT. Narendra God of Yoga